2015
DOI: 10.1007/s12192-014-0559-7
|View full text |Cite
|
Sign up to set email alerts
|

The global effect of heat on gene expression in cultured bovine mammary epithelial cells

Abstract: Heat stress (HS) in hot climates is a major cause that strongly negatively affects milk yield in dairy cattle, leading to immeasurable economic loss. The heat stress response of bovine mammary epithelial cells (BMECs) is one component of the acute systemic response to HS. Gene networks of BMECs respond to environmental heat loads with both intra-and extracellular signals that coordinate cellular and whole-animal metabolism. Our experimental objective was to characterize the direct effects of heat stress on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 32 publications
5
39
0
Order By: Relevance
“…So, we hypothesized that heat stress may induce the change of gene expression, finally leading to disordered ovarian function. In the present study, using DGE profiling of granulosa cells, we have demonstrated that thermal stress triggers a dramatic and complex program of altered gene expression in GCs similar to some patterns reported in other cell types exposed to thermal stress (Collier et al 2008;Li et al 2015). Some reported that thermal stress can regulate the RNA processing/translation, increase degradation of proteins, disrupt the cytoskeletal components, and alter metabolism process (Collier et al 2006;Sonna et al 2010).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…So, we hypothesized that heat stress may induce the change of gene expression, finally leading to disordered ovarian function. In the present study, using DGE profiling of granulosa cells, we have demonstrated that thermal stress triggers a dramatic and complex program of altered gene expression in GCs similar to some patterns reported in other cell types exposed to thermal stress (Collier et al 2008;Li et al 2015). Some reported that thermal stress can regulate the RNA processing/translation, increase degradation of proteins, disrupt the cytoskeletal components, and alter metabolism process (Collier et al 2006;Sonna et al 2010).…”
Section: Discussionsupporting
confidence: 82%
“…After 48 h of preculture, when cells attached to the bottom of the wells, the medium was replaced with medium of the same composition. Then cells were cultured at temperatures 38°C (control group) or 40.5°C (heat treatment group) for 2 h, and then the cells were cultured at 38°C for 12 h. Immediately after culture, the cells and culture media were collected for subsequent analyses (Li et al 2015).…”
Section: Heat Treatmentmentioning
confidence: 99%
“…Mammary tissues were obtained from three healthy Holstein dairy cows at the middle stage of lactation. In vitro cultures of mammary epithelial cells were prepared in accordance with the established methods by Dairy Science Institute of Nanjing Agricultural University (Li et al 2014). The cells were cultured in Dulbecco's modified Eagle's medium (DMEM) containing 4.5 mg/mL glucose and supplemented with 10% fetal bovine serum (Life Technologies, Gaithersburg, MD, USA) and 1% antibiotic-antimycotic solution (Sigma-Aldrich, St. Louis, MO, USA) in a humidified incubator, with 5% CO 2 at 38°C.…”
Section: Materials and Methods Bmec Isolation And Cell Culturementioning
confidence: 99%
“…In a previous study, we have found that heat stress could affect the function and gene expression of bovine mammary epithelial cells (BMECs); the response of BMECs to heat stress plays a vital role in regulating mammary function (Li et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation